Metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy

By combining vanadium-based solid hydrogen storage alloy designed with V-Ti-Cr alloy with low Ti/Cr ratio with high pressure gas cylinders, a composite hydrogen storage tank is solved, and a high-quality and high-volume hydrogen storage density is achieved.

CN119879046APending Publication Date: 2025-04-25BAOKUN (SHANGHAI) ENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510097354.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The volume and weight hydrogen storage density of existing metal hydride/high-pressure composite hydrogen storage systems is relatively low, making it difficult to have both high-quality hydrogen storage density and volume hydrogen storage density.

Method used

A V-Ti-Cr alloy with low Ti/Cr ratio is used to design a vanadium-based solid hydrogen storage alloy with low enthalpy change and high hydrogen release platform pressure, and combined with a high-pressure gas cylinder to form a metal hydride/high-pressure composite hydrogen storage tank.

Benefits of technology

A high volume hydrogen storage density ≥60 gH2/L and a high-quality hydrogen storage density ≥2.3 wt.%, which is significantly better than the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119879046A_ABST
    Figure CN119879046A_ABST
Patent Text Reader

Abstract

The invention relates to a metal hydride / high-pressure composite hydrogen storage tank based on a vanadium-based solid hydrogen storage alloy, and belongs to the technical field of hydrogen energy. The chemical formula of the vanadium-based solid hydrogen storage alloy is VxTiyCrz, the range of x is 50-80, the range of y is 4-12, and the range of y / z is 0.15-0.37; the vanadium-based solid hydrogen storage alloy is composed of a body-centered cubic single phase. The volume hydrogen storage density of the metal hydride composite hydrogen storage tank is 65-118 g / L, and the mass hydrogen storage density of the metal hydride composite hydrogen storage tank is 3.1-2.5 wt.%; the filling rate of the vanadium-based solid hydrogen storage alloy is 31%-70%. The obtained metal hydride composite hydrogen storage tank has the excellent performance that the high-volume hydrogen storage density is larger than or equal to 60 gH2 / L and the high-mass hydrogen storage density is larger than or equal to 2.3 wt.%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen energy, and in particular to a metal hydride / high-pressure composite hydrogen storage tank based on a vanadium-based solid hydrogen storage alloy. Background Art

[0002] The excessive use of non-renewable fossil fuels has brought about increasingly serious environmental pollution and energy crises. Hydrogen has the characteristics of wide sources, zero emissions and high energy efficiency, and is considered to be the most ideal clean energy. The hydrogen energy industry mainly includes three links: hydrogen production, storage and utilization. Since the density of hydrogen at room temperature and pressure is very low, only 0.0899 g / L, and the explosion limit is wide, the safe and efficient storage and transportation of hydrogen is the key technical bottleneck for the development of the hydrogen energy industry.

[0003] The existing hydrogen storage methods mainly include high-pressure gas, cryogenic liquid, metal hydride, etc. Cryogenic liquid hydrogen storage, deep cooling hydrogen to -253℃ to turn it into liquid hydrogen, but it consumes a lot of energy and has high costs. It is currently mainly used in special scenarios such as aerospace and military. High-pressure gaseous hydrogen storage, pressurizing hydrogen to 35-70 MPa, can achieve a high mass hydrogen storage density (3.0 ~ 6.0 wt%), and its volume hydrogen storage density is relatively low, only 22 ~ 35 kgH 2 / m 3 . Metal hydrides, including rare earth AB 5 Alloy, titanium series AB and AB 2 Hydrogen storage alloys, vanadium solid solution hydrogen storage alloys, etc., have a low effective mass hydrogen storage density of 1.4 ~ 2.5 wt% near room temperature, but the volume hydrogen storage density can reach 100 kgH 2 / m 3 above.

[0004] In order to obtain a hydrogen storage device with both high-quality hydrogen storage density and volume hydrogen storage density, the researchers designed a composite hydrogen storage system by combining the advantages of high-pressure hydrogen storage and metal hydride. 2 A 35MPa vehicle-mounted high-pressure composite tank was designed using Ti-Cr-Mn alloy. When the alloy filling amount was 30%, the volume hydrogen storage density of the composite tank was 49 gH 2 / L. Cao Zhijie et al. used AB-type ZrFe, Zr-Fe-Al and Zr-Fe-V alloys to compound with 35 MPa high-pressure hydrogen storage tanks. When the alloy filling amount was 50%, the mass hydrogen storage density of the tank was 1.8 wt.%, and the volume hydrogen storage density was 40 gH 2 / L. Zheng Mei et al. used AB 2The Ti-Cr-Fe-Mn alloy is composited with a 45 MPa high-pressure hydrogen storage tank, with a mass hydrogen storage density of 1.63 wt.%, and a hydrogen desorption platform pressure of 15-50 MPa at 318-338 K. Toyota uses AB 2 The Ti-Cr-Mn alloy was used as a hydrogen storage material to develop a 35 MPa high-pressure composite hydrogen storage tank with a total volume of 7 kg and a volumetric hydrogen storage density of 40 kgH. 2 / m 3 , the mass hydrogen storage density is 1.6 wt.%.

[0005] The above composite hydrogen storage systems generally use AB 2 And AB hydrogen storage alloy, because its mass hydrogen storage density generally does not exceed 1.8 wt.%, although the volume hydrogen storage density of the composite hydrogen storage tank can be increased after filling, it will lead to a low weight hydrogen storage density, generally only about 1.6 wt.%.

[0006] Compared with AB 2 Compared with AB alloy, the reversible hydrogen storage density of vanadium-based hydrogen storage alloy is higher, reaching more than 2.5 wt% at room temperature. Studies have shown that changing the content of V, Ti, and Cr elements can adjust the platform pressure and hydrogen storage performance of the alloy, especially the Ti / Cr value has a greater impact on the platform pressure of the alloy. Figure 1 The PCT curve of hydrogen storage alloy dehydrogenation shows that under the condition of full hydrogen, the dehydrogenation temperature remains unchanged, the higher the dehydrogenation platform pressure, the higher the effective dehydrogenation amount. Due to the serious hysteresis in the dehydrogenation and absorption process of vanadium-based hydrogen storage alloy (such as Figure 2 ), in order to obtain a high hydrogen release amount and hydrogen release platform, the alloy's hydrogen absorption process requires a higher hydrogen absorption pressure. The existing 35MPa high-pressure hydrogen storage system can increase the hydrogen pressure sufficiently for the high-platform vanadium-based solid hydrogen storage alloy to reach hydrogen absorption saturation, thereby achieving a higher hydrogen release amount. Therefore, the present invention proposes a metal hydride / high-pressure composite hydrogen storage technology based on vanadium-based hydrogen storage alloy, which simultaneously achieves high mass hydrogen storage density and volume hydrogen storage density. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy. The metal hydride composite hydrogen storage tank obtained by the present invention has both high volumetric hydrogen storage density ≥ 60 gH 2 / L and excellent performance of high-quality hydrogen storage density ≥2.3 wt.%.

[0008] The present invention designs a vanadium-based solid hydrogen storage alloy with low enthalpy change and high hydrogen release platform pressure by reducing the Ti / Cr ratio. When the hydrogen absorption pressure is ≥ 20 MPa, at 50 °C and cutoff 0.1 MPa, the vanadium-based solid hydrogen storage alloy (for example, V 57 Ti 6 Cr31 ) can be increased to more than 2.75 wt.% ( Figure 3 As shown), the volume hydrogen storage density reaches 118 gH 2 / L. In contrast, the reversible hydrogen storage capacity of vanadium-based solid hydrogen storage alloys is generally 2.2-2.5 wt.%, and the dehydrogenation platform pressure is relatively low (about 0.01-0.2 MPa at 50 °C).

[0009] The metal hydride / high-pressure composite hydrogen storage tank of the present invention is made of a vanadium-based solid hydrogen storage alloy with low enthalpy change and high hydrogen release platform pressure, which solves the problem of low volume and weight hydrogen storage density of existing metal hydride / high-pressure composite hydrogen storage systems, and simultaneously achieves a high volume hydrogen storage density of 65-118 g / L and a mass hydrogen storage density of 3.1-2.5 wt.%.

[0010] The vanadium-based solid hydrogen storage alloy with improved high hydrogen release platform and low enthalpy change of the present invention is characterized by a Ti / Cr ratio of 0.17 to 0.34, a body-centered cubic structure, and a hydrogen release enthalpy change of -33.6 kJ / mol·H 2 ≤ΔH≤-30.4 kJ / mol·H 2 , the hydrogen decomposition pressure is 10~23 MPa at 25~50℃.

[0011] The present invention aims at a metal hydride composite hydrogen storage tank based on a vanadium-based solid hydrogen storage alloy, comprising a vanadium-based solid hydrogen storage alloy, wherein the chemical formula of the hydrogen storage alloy is V x Ti y Cr z , wherein the range of x is 50-80, the range of y is 4-12, and the range of x / y is 0.15-0.37; the vanadium-based solid hydrogen storage alloy is composed of a body-centered cubic single phase.

[0012] In some embodiments of the present invention, the volumetric hydrogen storage density of the metal hydride composite hydrogen storage tank is 65-118 g / L, and the mass hydrogen storage density is 3.1-2.5 wt.%; The filling rate of the vanadium-based solid hydrogen storage alloy is 31% to 70%.

[0013] In some embodiments of the present invention, the vanadium-based solid hydrogen storage alloy comprises V 57 Ti 10 Cr 27 、V 57 Ti 5 Cr 33 、V 57 Ti 6 Cr 31 、V 69 Ti 6 Cr 17 and V69 Ti 4 Cr 20 One or more of .

[0014] In some embodiments of the present invention, the vanadium-based solid hydrogen storage alloy has a hydrogen release enthalpy change of -33.6 kJ / mol·H 2 ≤ΔH≤-30.4 kJ / mol·H 2 .

[0015] In some embodiments of the present invention, the vanadium-based solid hydrogen storage alloy has a hydrogen desorption pressure of 4 to 9 MPa and a hydrogen absorption pressure of 10 to 24 MPa at 25°C; The dehydrogenation pressure is 10~23 MPa at 25-50℃, and the dehydrogenation amount is ≥2.6 wt.% at 0.1 MPa.

[0016] In some embodiments of the present invention, the method for preparing the vanadium-based solid hydrogen storage alloy comprises the following steps: (1) Take raw materials V ingot, Ti ingot and Cr ingot, mix them according to the chemical formula of vanadium-based solid hydrogen storage alloy, put them into a copper crucible, and place them in a vacuum heating device; (2) The vacuum heating device is cleaned with argon gas at least three times, then evacuated, filled with argon gas, and the alloy is repeatedly turned over and melted at least four times using an electric arc, and the cast alloy is taken out after cooling, and then heat treated to obtain an annealed vanadium-based solid hydrogen storage alloy after cooling; (3) Crushing and sieving the annealed vanadium-based solid hydrogen storage alloy obtained in step (2) to obtain the vanadium-based solid hydrogen storage alloy.

[0017] In some embodiments of the present invention, in step (1), the purity of the raw materials V ingot, Ti ingot and Cr ingot is ≥ 99 wt.%.

[0018] In some embodiments of the present invention, in step (2), the vacuum degree of the vacuum heating device is less than or equal to 5×10 -4 MPa.

[0019] In some embodiments of the present invention, in step (2), the heat treatment temperature is 1200-1400° C. and the time is 2-3 h.

[0020] In some embodiments of the present invention, in step (3), the inert gas is selected from argon.

[0021] In some embodiments of the present invention, in step (3), the annealed vanadium-based solid hydrogen storage alloy is crushed to 0.5-3 mm and passed through a 6-8 mesh sieve.

[0022] Furthermore, the metal hydride composite hydrogen storage tank is a high-pressure solid-state composite hydrogen storage tank, which is mainly composed of a vanadium-based solid-state hydrogen storage alloy and a high-pressure gas cylinder. The high-pressure gas cylinder adopts a type IV bottle structure, a plastic liner and an outer carbon fiber winding; the maximum volume hydrogen storage density of the composite hydrogen storage tank reaches 124 g H 2 / L, the maximum mass hydrogen storage density reaches 3.1 wt.%, and the tank size is designed according to GB / T 42612-2023.

[0023] The above technical solution of the present invention has the following advantages compared with the prior art: (1) The present invention proposes a V-Ti-Cr alloy with a low Ti / Cr ratio, which is characterized by a Ti / Cr ratio range of 0.15 to 0.37, a body-centered cubic structure, and a hydrogen release enthalpy change of -33.6 kJ / mol·H 2 ≤ΔH≤-30.4 kJ / mol·H 2 The dehydrogenation pressure is 10-23 MPa at 25-50°C. At 50°C, the cutoff value is 0.1 MPa, and the maximum dehydrogenation amount reaches 2.75 wt%, which exceeds the vanadium-based solid hydrogen storage alloys reported in existing literature.

[0024] (2) The present invention proposes a V-Ti-Cr alloy with a low Ti / Cr ratio, which has a maximum hydrogen release of 2.75 wt% at 50 °C and a cutoff pressure of 0.1 MPa, such as the commonly used AB 5 Type (1.4 wt%), AB 2 type (1.8 wt%) alloy were 96% and 53% higher respectively.

[0025] (3) The vanadium-based solid hydrogen storage alloy / high-pressure hydrogen storage composite hydrogen storage tank proposed in the present invention can simultaneously achieve a high volume hydrogen storage density of 65~118 kgH 2 / m 3 The high mass hydrogen storage density is 3.1~2.5 wt.%, which is significantly better than the existing reports. For example, the AB developed by Toyota 2 The composite hydrogen storage tank with a hydrogen storage alloy of 35 MPa has a volumetric hydrogen storage density of only 40 kgH 2 / m 3 , the mass hydrogen storage density is only 1.6 wt.%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 It is a schematic diagram of the PCT curve of the hydrogen storage alloy in the prior art.

[0027] Figure 2It is a schematic diagram of the PCT curve of hydrogen absorption and desorption of hydrogen storage alloys at the same temperature in the prior art.

[0028] Figure 3 is the V obtained in Example 2 of the present invention 57 Ti 6 Cr 31 PCT curve of hydrogen desorption of vanadium-based solid hydrogen storage alloy at 50 ℃.

[0029] Figure 4 is the V obtained in Example 1 of the present invention 57 Ti 10 Cr 27 PCT curve of hydrogen desorption of vanadium-based solid hydrogen storage alloy at 50 ℃.

[0030] Figure 5 is the V obtained in Example 1 of the present invention 57 Ti 10 Cr 27 SEM image of vanadium-based solid hydrogen storage alloy.

[0031] Figure 6 is the V obtained in Example 1 of the present invention 57 Ti 10 Cr 27 EDS surface scanning results of vanadium-based solid hydrogen storage alloy.

[0032] Figure 7 is the V obtained in Example 1 of the present invention 57 Ti 10 Cr 27 XRD spectrum of vanadium-based solid hydrogen storage alloy.

[0033] Figure 8 It is a schematic diagram of the 35 MPa high-pressure hydrogen / metal hydride composite hydrogen storage tank of the present invention.

[0034] Fig. 9 It is the relationship between the filling rate of the vanadium-based solid hydrogen storage alloy and the volume and mass hydrogen storage density of the composite hydrogen storage tank in Examples 1 and 2 of the present invention.

[0035] Fig.10 is the V obtained in Example 2 of the present invention 57 Ti 6 Cr 31 SEM image of vanadium-based solid hydrogen storage alloy.

[0036] Fig.11 is the V obtained in Example 2 of the present invention 57 Ti 6 Cr 31 EDS surface scanning results of vanadium-based solid hydrogen storage alloy.

[0037] Fig.12is the V obtained in Example 2 of the present invention 57 Ti 6 Cr 31 XRD spectrum of vanadium-based solid hydrogen storage alloy.

[0038] Fig.13 is the comparative example 1 of the present invention (Ti 0.5 Zr 0.15 )Mn 0.8 CrFe 0.2 PCT curve of hydrogen desorption of vanadium-based solid hydrogen storage alloy at 50 ℃.

[0039] Fig.14 It is AB in comparative example 1 of the present invention 2 Relationship between alloy filling rate and volume and mass hydrogen storage density of composite hydrogen storage tank.

[0040] Fig.15 is La in Comparative Example 2 of the present invention 0.8 Ce 0.2 Ni 5 PCT curve of hydrogen desorption of vanadium-based solid hydrogen storage alloy at 50 ℃.

[0041] Fig.16 It is AB in comparative example 2 of the present invention 5 Relationship between alloy filling rate and volume and mass hydrogen storage density of high-pressure solid composite hydrogen storage tank.

[0042] Fig.17 The TiFe 0.85 Mn 0.05 PCT curve of hydrogen desorption of vanadium-based solid hydrogen storage alloy at 50 ℃.

[0043] Fig.18 It is the relationship between the AB alloy filling rate and the volume and mass hydrogen storage density of the composite hydrogen storage tank in comparative example 3 of the present invention.

[0044] Explanation of the reference numerals in the drawings in the specification: 1. Dome protective cover of Type IV bottle; 2. Carbon fiber composite material shell; 3. Polymer material lining; 4. Vanadium-based solid hydrogen storage alloy bed; 5. Valve; 6. Sleeve; 7. Temperature sensor. DETAILED DESCRIPTION

[0045] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0046] Embodiment 1: This embodiment provides a vanadium-based solid hydrogen storage alloy, which is specifically as follows: 1. V 57 Ti 10 Cr27 Alloy preparation method: (1) Take V, Ti and Cr ingots with a purity of ≥ 99 wt.%, weigh them according to the proportion and put them into the crucible.

[0047] (2) Close the furnace, clean the furnace with high-purity argon (≥ 99.99%) three times, and then evacuate to 10 -4 MPa, and then filled with 0.1 MPa of high-purity argon as a protective gas, and used an electric arc to repeatedly turn the vanadium-based solid hydrogen storage alloy over and melt it for 4 times. After the furnace was cooled, the cast vanadium-based solid hydrogen storage alloy was taken out, and then the cast vanadium-based solid hydrogen storage alloy was placed in a vacuum molybdenum wire furnace and heat treated at 1400°C for 2.5 h. After cooling with the furnace, the annealed vanadium-based solid hydrogen storage alloy was obtained.

[0048] (3) The annealed vanadium-based solid hydrogen storage alloy obtained in step (2) is crushed into pieces of 0.5-3 mm and passed through a 6-mesh sieve to obtain the vanadium-based solid hydrogen storage alloy.

[0049] 2. Characterization: The obtained vanadium-based solid hydrogen storage alloy was structurally characterized. The SEM, EDS and XRD of the vanadium-based solid hydrogen storage alloy were as follows: Figure 5 , 6 and 7.

[0050] 3. Performance test: Fig. 9 V 57 Ti 10 Cr 27 The relationship curve between the alloy filling rate and the weight hydrogen storage density and volume hydrogen storage density of the high-pressure composite hydrogen storage tank. When the filling rate is 31%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 65 g / L, and the mass hydrogen storage density is 3.1wt.%. When the filling rate reaches 70%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 118 g / L, and the mass hydrogen storage density is 2.5wt.%.

[0051] Figure 4 PCT curve of hydrogen release at 50℃: Vanadium-based solid hydrogen storage alloy adopts V 57 Ti 10 Cr 27 When the vanadium-based solid hydrogen storage alloy is used, the enthalpy change during hydrogen release is ΔH = ‒33.6 kJ / mol H 2 The hydrogen desorption platform pressure at 25°C is 2.4 MPa, and at 50°C it is 6.5 MPa.

[0052] Embodiment 2: This embodiment provides a vanadium-based solid hydrogen storage alloy, which is specifically as follows: 1. V 57 Ti 6 Cr31 Alloy preparation method: (1) Take V, Ti and Cr ingots with a purity of ≥ 99 wt.%, weigh them according to the proportion and put them into the crucible.

[0053] (2) Close the furnace, clean the furnace with high-purity argon (≥ 99.99%) three times, and then evacuate to 10 -4 MPa, and then filled with 0.1 MPa of high-purity argon as a protective gas, and used an electric arc to repeatedly turn the vanadium-based solid hydrogen storage alloy over and melt it for 4 times. After the furnace cooled down, the cast alloy was taken out, and then the cast vanadium-based solid hydrogen storage alloy was placed in a vacuum molybdenum wire furnace and heat treated at 1400°C for 2.5 h. After cooling with the furnace, the annealed vanadium-based solid hydrogen storage alloy was obtained.

[0054] (3) crushing the annealed vanadium-based solid hydrogen storage alloy obtained in step (2) into pieces of 0.5-3 mm and passing through a 6-mesh sieve to obtain the V 57 Ti 6 Cr 31 alloy.

[0055] 2. Characterization: The obtained V 57 Ti 6 Cr 31 Alloy structure characterization, V 57Ti6 Cr 31 The SEM, EDS and XRD of the alloys are shown in Figure 2. Fig.10 , 11 and 12.

[0056] 3. Performance test: Hydrogen storage alloy adopts V 57 Ti 6 Cr 31 When the vanadium-based solid hydrogen storage alloy is used, the enthalpy change during hydrogen release is ΔH = ‒30.4 kJ / mol H 2 The hydrogen desorption platform pressure at 25℃ is 5.0 MPa, and at 50℃ it is 11.6 MPa. The PCT curve of hydrogen desorption at 50℃ is as follows: Figure 3 shown.

[0057] Similar to Example 1, when the filling rate is 31%, the volumetric hydrogen storage density of the high-pressure composite hydrogen storage tank is 65 g / L, and the mass hydrogen storage density is 3.1 wt.%. When the filling rate reaches 70%, the volumetric hydrogen storage density of the high-pressure composite hydrogen storage tank is 118 g / L, and the mass hydrogen storage density is 2.5 wt.%.

[0058] Comparative Example 1: Hydrogen storage alloy adopts AB 2 Alloy (Ti 0.5 Zr 0.15 )Mn0.8 CrFe 0.2 ),AB 2 The alloy releases 1.7 wt.% hydrogen at 0.1 MPa at 50 °C. Fig.13 AB 2 PCT curve of alloy. AB 2 The alloy density is 6.0 g / cm 3 , Fig.14 AB 2 The relationship curve between alloy filling rate and weight hydrogen storage density and volume hydrogen storage density of high-pressure composite hydrogen storage tank. When the filling rate is 26%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 39 g / L, and the mass hydrogen storage density is 2.05 wt.%. When the filling rate reaches 70%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 73 g / L, and the mass hydrogen storage density is 1.58 wt.%. Under the premise of the same filling rate (for example, 70%), based on AB 2 The volume hydrogen storage density of the alloy composite hydrogen storage tank is only 62% of that of the vanadium-based solid hydrogen storage alloy in Example 1, and the mass hydrogen storage density is only 63% of that of the vanadium-based solid hydrogen storage alloy in Example 1.

[0059] Comparative Example 2: Hydrogen storage alloy adopts AB 5 Alloy (La 0.8 Ce 0.2 Ni 5 ),AB 5 The alloy releases 1.5 wt.% hydrogen at 0.1 MPa at 50 °C. Fig.15 AB 5 PCT curve of alloy. AB 5 The alloy density is 8.9 g / cm 3 , Fig.16 AB 5 The relationship curve between alloy filling rate and weight hydrogen storage density and volume hydrogen storage density of high-pressure composite hydrogen storage tank. When the filling rate is 26%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 43 g / L, and the mass hydrogen storage density is 1.98 wt.%. When the filling rate reaches 70%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 83 g / L, and the mass hydrogen storage density is 1.36 wt.%. Under the premise of the same filling rate (for example, 70%), based on AB 5 The volume hydrogen storage density of the alloy composite hydrogen storage tank is only 70% of that of the vanadium-based solid hydrogen storage alloy in Example 1, and the mass hydrogen storage density is only 54% of that of the vanadium-based solid hydrogen storage alloy in Example 1.

[0060] Comparative Example 3: The hydrogen storage alloy is AB alloy (such as TiFe 0.85 Mn 0.05), the amount of hydrogen released by AB alloy at 50 ℃ and 0.1 MPa is 1.7 wt.%, Fig.17 The PCT curve of AB alloy. The density of AB alloy is 6.0 g / cm 3 , Fig.18 The relationship curve between the filling rate of AB alloy and the weight hydrogen storage density and volume hydrogen storage density of the high-pressure composite hydrogen storage tank. When the filling rate is 31%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 51 g / L, and the mass hydrogen storage density is 2.09 wt.%. When the filling rate reaches 70%, the volume hydrogen storage density of the high-pressure composite hydrogen storage tank is 87 g / L, and the mass hydrogen storage density is 1.66 wt.%. Under the premise of the same filling rate (for example, 70%), the volume hydrogen storage density of the composite hydrogen storage tank based on AB alloy is only 74% of the vanadium-based solid hydrogen storage alloy in Example 1, and the mass hydrogen storage density is only 66% of the vanadium-based solid hydrogen storage alloy in Example 1.

[0061] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A metal hydride / high-pressure composite hydrogen storage tank based on a vanadium-based solid hydrogen storage alloy, characterized in that: A vanadium-based solid hydrogen storage alloy having a chemical formula of V x Ti y Cr z , wherein the range of x is 50-80, the range of y is 4-12, and the range of y / z is 0.15-0.37; the vanadium-based solid hydrogen storage alloy consists of a body-centered cubic single phase.

2. A metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 1, characterized in that: The volumetric hydrogen storage density of the metal hydride / high-pressure composite hydrogen storage tank is 65-118 g / L, and the mass hydrogen storage density is 3.1-2.5 wt.%; the filling rate of the vanadium-based solid hydrogen storage alloy is 31%-70%.

3. A metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 1, characterized in that: The vanadium-based solid hydrogen storage alloy comprises V 57 Ti 10 Cr 27 、V 57 Ti5Cr 33 、V 57 Ti6Cr 31 、V 69 Ti6Cr 17 and V 69 Ti4Cr 20 One or more of .

4. A metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 1, characterized in that: The dehydrogenation enthalpy change of the vanadium-based solid hydrogen storage alloy is -33.6 kJ / mol·H2≤ΔH≤-30.4 kJ / mol·H2.

5. The metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 1, characterized in that: The vanadium-based solid hydrogen storage alloy has a dehydrogenation pressure of 4-9 MPa and a hydrogen absorption pressure of 10-24 MPa at 25° C.; a dehydrogenation pressure of 10-23 MPa at 25-50° C., and a dehydrogenation amount of 0.1 MPa of ≥2.6 wt.%.

6. A metal hydride / high-pressure composite hydrogen storage tank based on a vanadium-based solid hydrogen storage alloy according to any one of claims 1 to 5, characterized in that: The preparation method of vanadium-based solid hydrogen storage alloy comprises the following steps: (1) Take raw materials V ingot, Ti ingot and Cr ingot, mix them according to the chemical formula of vanadium-based solid hydrogen storage alloy, put them into a non-consumable vacuum arc furnace, and place them in a vacuum heating device; (2) The vacuum heating device is cleaned with argon gas at least three times, then evacuated, and then filled with argon gas, and the alloy is repeatedly turned over and melted at least four times using an electric arc, and the cast alloy is taken out after cooling, and then heat treated to obtain an annealed vanadium-based solid hydrogen storage alloy after cooling; (3) Crushing and sieving the annealed vanadium-based solid hydrogen storage alloy obtained in step (2) to obtain the vanadium-based solid hydrogen storage alloy.

7. A metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 6, characterized in that: In step (1), the purity of the raw materials V ingot, Ti ingot and Cr ingot is ≥ 99 wt.%.

8. The metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 6, characterized in that: In step (2), the vacuum degree of the vacuum heating device is less than or equal to 5×10 -4 MPa.

9. A metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 6, characterized in that: In step (2), the heat treatment temperature is 1200~1400°C and the time is 2~3 h.

10. A metal hydride / high-pressure composite hydrogen storage tank based on vanadium-based solid hydrogen storage alloy according to claim 6, characterized in that: In step (3), the inert gas is selected from argon; The annealed vanadium-based solid hydrogen storage alloy was crushed to 0.5~3 mm.